PHARMACOLOGICAL EVALUATION OF CINNAMALDEHYDE AGAINST DMBA-INDUCED SKIN CANCER IN ALBINO MICE - KHATOON, ASIYA; AGARWAL, SORABH KUMAR; BUTOOL, SANA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The primary objective of this study was to assess the pharmacological activity of Cinnamaldehyde (CA) obtained from cinnamon bark in 7, 12-Dimethylbenz antharacene (DMBA)-induced skin cancer in albino mice and to assess the important cell antioxidant enzymes levels which play an important role in cancer. Methods: Cinnamon bark was collected to obtain CA phytochemical screening of extract was performed. Then pharmacological screening of extract was done in albino mice with skin cancer, after 12 weeks of observation, the animal was sacrificed, the skin samples were collected and various parameters were assessed and at the end histopathological studies were performed. Further statistical methods were applied to analyze the results. Results: The results revealed that CA produces significant increase in cell anti-oxidant enzymes such as superoxide dismutase, catalase, and glutathione peroxidase content. It is also reported that it has inhibited the activity of lactate dehydrogenase and levels of lipid peroxidation at the same time which are responsible for cell damage. Conclusion: The present study shows that CA obtained from cinnamon bark consist of significant anti-cancer activity against DMBA-induced skin cancer in albino mice.